Effects on Quadriceps Muscle Strength Using EMG in Supervised vs Unsupervised Post-Operative Anterior Crucial Ligament Reconstruction (Medico Legal Update, 2020)
Anterior crucial ligament (ACL) injury is one of the most common ligament injuries in the knee. TheACL injury is the anterior ligament tear or sprain (ACL). The objective of this paper is to compare theeffectiveness, recovery rate and the variance in the affected and non-affected limbs muscle strength/activation potential readings of both knees in supervised v/s unsupervised groups of patients afterundergone ACL reconstruction surgery at RML Hospital Delhi. The participants were divided into twogroups (A-Supervised, and B-Unsupervised) through random sampling. The supervised exercise in groupa performed according to the WILK protocol at RML hospital, and un-supervised group B performed thesame WILK protocol at home. The method adopted for this study is to compare both Pre-operative andPost-Operative quadriceps(vastus medialis and vastus latralis) EMG readings of the respondents has beenrecorded using NEURON SPECTRUM 5 using NEUROSOFT Neuro-MEP.NET software at RML HospitalDelhi. The study findings indicated the significant difference in recovery rate as well as the difference inbetween supervised v/s unsupervised groups i.e. The average pre-operative-VM values of EMG- affectedfor supervised was 97.1?V, and for unsupervised was 94.2?V and the average post-operative-VM values ofEMG for supervised was 130.1?V (36% variance), and for unsupervised was 95.2 ?V (1% variance). Theaverage pre-operative-VM values of EMG- normal for supervised was 135.8 ?V, and for unsupervised was139 ?V and the average post-operative-VM values of EMG for supervised was 135.1 ?V (-7% variance),and for unsupervised was 135.7 ?V (-6% variance).